2021
DOI: 10.1002/ccd.29694
|View full text |Cite
|
Sign up to set email alerts
|

Changes in surgical revascularization strategy after fractional flow reserve

Abstract: Aims: In the randomized GRAFFITI trial, surgeons drew their strategy based on coronary angiography. When patients were randomized to fractional flow reserve (FFR)guidance, surgeons were informed of the FFR values and asked to redraw their strategy. The aim of this study was to investigate the changes induced by FFR knowledge.Methods and Results: The intended and performed strategy (before and after FFR) were compared. Among 172 patients, 84 with 300 lesions were randomized to the FFR-guided group. The intended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Coronary artery bypass grafting (CABG) is an invasive procedure that supplies extra blood flow to the heart in patients with extensive CAD via surgical implantation of additional conduits. Whilst observational studies have shown a significant correlation between preoperative FFR and graft patency at follow-up, RCTs have failed to confirm such findings 22,23 . The FARGO and the GRAFFITI RCTs, comparing FFR-and angio-guided surgical strategies, failed to demonstrate improved 6-12 month graft patency nor advantages in terms of clinical events 22 .…”
Section: Cabgmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary artery bypass grafting (CABG) is an invasive procedure that supplies extra blood flow to the heart in patients with extensive CAD via surgical implantation of additional conduits. Whilst observational studies have shown a significant correlation between preoperative FFR and graft patency at follow-up, RCTs have failed to confirm such findings 22,23 . The FARGO and the GRAFFITI RCTs, comparing FFR-and angio-guided surgical strategies, failed to demonstrate improved 6-12 month graft patency nor advantages in terms of clinical events 22 .…”
Section: Cabgmentioning
confidence: 99%
“…Whilst observational studies have shown a significant correlation between preoperative FFR and graft patency at follow-up, RCTs have failed to confirm such findings 22,23 . The FARGO and the GRAFFITI RCTs, comparing FFR-and angio-guided surgical strategies, failed to demonstrate improved 6-12 month graft patency nor advantages in terms of clinical events 22 . In GRAFFITI, FFR-guidance allowed a simplification of the surgical intervention in up to 50% of patients, by reducing the number of anastomoses and by increasing off-pump grafting and minimally invasive surgery 22,24 .…”
Section: Cabgmentioning
confidence: 99%